2011
DOI: 10.1108/02686901211186117
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of corporate reporting on the internet

Abstract: PurposeThe primary objective of this study is to investigate the utilization of the internet by the Turkish companies listed on the Istanbul Stock Exchange (ISE) for corporate reporting; to determine the company characteristics that influence the information disclosure level on the internet; and to investigate whether there is a significant difference between the firms listed in the Corporate Governance Index of the ISE and those that are not, in terms of level of disclosure on the corporate web sites.Design/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 31 publications
1
17
0
1
Order By: Relevance
“…Those companies are obliged to publicly communicate financial information and produce quarterly management reports, make announcements to investors, disclose important events by press releases, and inform stakeholders about social and environmental responsibility activities through their corporate websites. As evidenced by Uyar (2012), companies utilise the internet actively as a communication tool for investor relations by disclosing financial and non-financial information. However, some items are not disclosed as much as others that require additional developments to increase the transparency of the companies.…”
Section: Determinants Of Corporate Reporting On the Internetmentioning
confidence: 99%
See 4 more Smart Citations
“…Those companies are obliged to publicly communicate financial information and produce quarterly management reports, make announcements to investors, disclose important events by press releases, and inform stakeholders about social and environmental responsibility activities through their corporate websites. As evidenced by Uyar (2012), companies utilise the internet actively as a communication tool for investor relations by disclosing financial and non-financial information. However, some items are not disclosed as much as others that require additional developments to increase the transparency of the companies.…”
Section: Determinants Of Corporate Reporting On the Internetmentioning
confidence: 99%
“…According to FASB (2000), six key motives can drive the level of financial information disclosure: (1) reducing the cost and time to distribute information; (2) communicating with previously unidentified consumers of information; (3) supplementing traditional disclosure practices; (4) increasing the amount and type of data disclosed; (5) improving access to potential investors form small companies; and (6) up-to-date information through regular maintenance of websites. However, other practical issues should be considered, such as reliability and selective reporting (Uyar, 2012). Basuony and Mohamed (2014) and Aly et al (2010) have found that large companies tend to disclose more financial information in order to reduce information asymmetry and also reduce agent costs.…”
Section: Determinants Of Corporate Reporting On the Internetmentioning
confidence: 99%
See 3 more Smart Citations